Brainstorming Technique in Assisting Students’ Writing Activity at English Education Study Program of IAIN MANADO - Halimah, Nur; Saini, Fadhlan; Saud, Indah Wardaty; Santoso, Agung Budi; Abdullah, Nurul Putri (Institut Agama Islam Negeri (IAIN) Manado, 2024)
The objective of this study was to determine to what extent of brainstorming technique in assisting the writing activities of third semester students in English Education Study Program. The researcher used a mixed-method research approach. In this study, the researcher used research instruments; questionnaires and interviews. The participants in this study were eighteen students and an English Lecturer of English Education Study Program at IAIN Manado. The data were analyzed trough involving data reduction, data display and conclusions. Based on results found by the researcher, 92.77% of students responded positively to the use of brainstorming technique in writing activities. It is confirmed by the results of interviews that students feel helpful and valuable when using brainstorming technique in writing activities, such as collecting ideas to be directed and structured. On the other hand, 7.23% of students responded negatively to this technique. Moreover, from the result of interviews students also said that writing activities using brainstorming technique were practical and helpful in collecting ideas and thoughts in writing a text. It can be proven by looking at the positive responses, which include interesting, fun, motivated, enjoyable, effective and creative.Keywords: brainstorming, technique, writing activities